2019
DOI: 10.1007/s40520-019-01163-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of osteoarthritis on activities of daily living: does joint site matter?

Abstract: Background We consider the relationships between a clinical and radiological diagnosis of knee or hip OA and activities of daily-living (ADL) in older adults. Methods Data were available for 222 men and 221 women from the Hertfordshire Cohort Study (HCS) who also participated in the UK component of the European Project on Osteoarthritis (EPOSA). Participants completed the EuroQoL survey where they reported if they had difficulties with mobility, self-care, usual activities and movement around their house. Hip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 26 publications
3
67
2
2
Order By: Relevance
“…The pathologies of these diseases are highly variable, but all include a component of joint inflammation. Patients with high disease activity typically have impaired quality of life and activities of daily living (4)(5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…The pathologies of these diseases are highly variable, but all include a component of joint inflammation. Patients with high disease activity typically have impaired quality of life and activities of daily living (4)(5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation as to why polypharmacy is associated with poorer physical function in women but not men in our cohort are sex differences in the type and severity of NCDs. A higher proportion of women than men in our cohort reported osteoarthritis (43.4% vs 33.8%) and rheumatoid arthritis (5.0% and 4.5%) which are disorders whose detrimental impact on physical functioning is well documented [29]. Additionally, biological differences between men and women may play a role; it has previously been shown that the sex of the patient can have profound influences on drug metabolism, efficacy and therefore adverse effects [30].…”
Section: Discussionmentioning
confidence: 68%
“…4,[6][7][8][9] OA of major joints, such as hip or knee, is associated with increasing and sometimes intolerable pain and movement disabilities10 that, with the progression of the disease, limit not only the professional performance, but also the everyday METHODS activities. 11 Several non-pharmacological (body weight loss, muscle strength-increasing exercises, physiotherapy) and pharmacological regimens (non-steroidal anti-inflammatory drugs po or im, intraarticular injections of viscosupplementation with hyaluronic acid, corticosteroids or biologicals) are used to treat this very painful and disabling condition. 12 Total knee arthroplasty (TKA) remains an ultimum refugium for the patients with end-stage osteoarthritis and its prevalence is also on the rise, along with the prevalence of OA.…”
Section: Multimodal Neural Block Analgesia Versus Morphine Analgesiamentioning
confidence: 99%